PREVALENCE AND INTENSITY OF TRYPANOSOMA EVANSI INFECTION IN HORSE at THE KABARU VILLAGE, SUBDISTRICT RINDI, EAST SUMBA REGENCY - Ndiha, Mersy Rambu Maramba; Apsari, Ida Ayu Pasti; Dwinata, I Made (Buletin Veteriner Udayana, 2018)
Surra is a parasitic disease caused by Trypanosoma evansi. The incidence of trypanosomiasis was influenced by geographical conditions, management system, vector, and host. The aim of this research is to determine the prevalence and intensity of T. evansi infection in horse in Kabaru village, subdistrict Rindi. The sample used was blood from 100 horses taken from Kabaru Village. Blood collected was done through a jugular vein and a thin blood smear were made then stained with Giemsa 10%. Preparations of blood smear were examined under microscope to determine the T. evansi infection and intensity were calculated on average number of T. evansi in 100 red blood cells. The result showed that 8% of blood sample infected by T. evansi with the infection intensity of 13-71 parasites with an average number of 34.5 ± 22.7. The prevalence of sex-based infections was found in males at 12% and females at 6.7%. There was no significant difference in prevalence of T. evansi infection between male and female horse.